PROPOSED BUSINESS STRATEGY FOR TEXTILE COMPANY USING DIAMOND STRATEGY CASE STUDY: CV KARA SYANDANA (The Indonesian Journal of Business Administration, 2019)
Fabrics are now valued as necessity because the need for clothing is one of the main needs of humans, making the fabric manufacturing business now has potential to become a growing business. CV Kara Syandana is a company engaged in fabric manufacturing and become legal entity since 2017. The products offered by CV Kara Syandana are cotton fabrics with various levels of thickness and various colors. Nowadays, many businesses that offer products in the same category as CV Kara Syandana, making the market of fabrics to be fiercely competitive, and problem arise for companies that reducing the number of sales. Aknowledged that condition is not good for the company, CV Kara Syandana must be able to find a way to win competition in the market.The results of the research shown that the company has the strength of great quality of the product and the speed of delivery, moreover opportunity comes from polyester fabric that has potential market. Therefore by using the facts found, a business strategy that was designed using diamond strategy as the framework.By formulating using a diamond strategy, the arena that chosen are consumers who focus on quality over price, then differentiate to prioritize quality factors with a focus on fabric softness and durability. After that the vehicle chosen is to use an alliance and internal development, with the staging stage it will implement a strategy of flanking into poliester market. And then implementation will be carried out using a business canvas model providing recommendations such as the production of new types of fabric, opening a shop as a showcase for the consumer, and maintaining the quality of fabric and the speed of fabric delivery.Keywords : Business Strategy, Competition, Cotton, Diamond Strategy, Fabric Manufacturing